Analisis Butir Soal Ditinjau Dari Sains Sebagai Produk dan Jenjang Kognitif Soal USBN Mata Pelajaran IPA SD Kabupaten Empat Lawang Tahun Pelajaran 2018/2019 dan 2019/2020 - Mei Feri Zami Zami; Irwan Koto; Endang Widi Winarni (UNIB Press, 2022)
This study aims to describe the nature of science as a product and cognitive level of USBN in elementary science subjects. This type of research is descriptive quantitative research. The subject of the study was USBN questions for science subjects at the Empat Lawang Regency Elementary School. The object of this research is the proportion of the nature of science as a product and level of items. The research instrument is a document in the form of a sheet of the results of the analysis of the nature of science and cognitive level. The percentage of science as a product and cognitive level were analyzed and calculated according to the agreement of the raters. The results of the study show that: (1) The percentage of the nature of science as a product of the 2018/2019 USBN questions: facts 26 questions (65%), the concept opened by 14 questions (35%), and there are no questions on principle indicators, laws, and theory . The percentage of the nature of science as a product of the USBN Science Subject matter for 2019/2020: facts found 34 questions (85%), the concept opened with 6 questions (15%), and there were no questions for principle, law, and theory indicators. Percentage level of knowledge about 2018/2019: understanding (C2) 4 questions (10.00%), applying (C3) and analyzing (C4) have the same number of 14 questions (35.00%), (3) discovery (C5 ) 8 questions (20,000%); and (4) there is no question of remembering, remembering (C1) and creating (C6). Percentage of cognitive level about USBN Year 2019/2020: understanding (C2) 6 questions (15.00%), applying (C3) 16 (40.00%), analyzing (C4) 16 questions (40.00%), developing ( C5) 2 questions (5.00%); and (5) there are no questions included in the ranks of remembering (C1) and creating (C6). Thus, it can be said that the quality of the USBN questions for the science subjects of the Empat Lawang Elementary School in the 2018/2019 and 2019/2020 academic years is quite good from the percentage of science as a product and improvement